Extremely rapid endocytosis mediated by the mannose receptor of sinusoidal endothelial rat liver cells. - Magnusson, S (1989)
Isolated sinusoidal endothelial rat liver cells (EC) in suspension bound and internalized ovalbumin, a mannose-terminated glycoprotein, in a saturable manner. The binding and uptake were Ca2+-dependent and were effectively inhibited by alpha-methyl mannoside and yeast mannan, but not by galactose or asialoglycoproteins. This corresponds to the binding specificity described for the mannose receptor of macrophages and non-parenchymal liver cells. Binding studies indicated a surface pool of 20,000-25,000 mannose receptors per cell, with a dissociation constant of 6 x 10(-8) M. Uptake and degradation of ovalbumin by isolated EC were inhibited by weak bases and ionophores which inhibit acidification of endocytic vesicles and dissociation of receptor-ligand complexes. Cycloheximide had no effect on uptake or degradation. Degradation, but not uptake, was inhibited by leupeptin. We conclude that ovalbumin dissociates from the mannose receptors in the endosomal compartment and the receptors are recycled to the cell surface, while the ovalbumin is directed to the lysosomes for degradation. A fraction of the internalized ovalbumin was recycled intact to the cell surface and escaped degradation (retroendocytosis). The rate of internalization of ovalbumin by isolated EC was very fast, with a Ke (endocytotic rate constant) of 4.12 min-1, which corresponds to a half-life of 10 s for the surface pool of receptor-ligand complexes. To our knowledge, this is the highest Ke reported for a receptor-mediated endocytosis system.